Strongly starlike functions associated with the Dziok-Srivastava operator - Liu, Jin-Lin (Tamkang Journal of Mathematics, 2004)
In terms of the Dziok-Srivastava operator, we introduce and study some new classes of strongly starlike functions. Certain properties of these subclasses are studied.